Mentzer index as a screening tool for iron deficiency anemia in 6-12-year-old children - Sri Lestari S. Alam; Rini Purnamasari; Erial Bahar; Kemas Ya'kub Rahadian (Paediatrica Indonesiana, 2014)
Background There is a high prevalence of iron deficiency anemia (IDA) in Indonesia. Iron deficiency anemia impairs the growth and development process in children. The reference standard to diagnose IDA is serum ferritin level. Since this test is expensive and rare not widely available, an inexpensive, simpler testis needed. The Mentzer index (mean corpuscular volume/red blood cell or MCV JRBC) has been used to identitY hypochromic-microcytic anemia with good validity.Objective To assess the validity of the Mentzer index for diagnosing IDA by comparing Mentzer indexes to serum ferritin and to define an optimal Mentzer index cut off point with good sensitivity and specificity.Methods The study was a diagnostic test with cross-sectional design. Subjects were collected by multistage, random sampling, from April to May 2013 at 18 elementary schools in Palembang. The study had a survey phase and diagnostic test phase. Subjects were aged 6-12 years with hypochromic-microcytic anemia. We examined complete blood counts to diagnose hypochromic-microcytic anemia, calculated Mentzer indexes, and measured serum ferritin levels of our subjects. We analyzed the validity of Mentzer index compared to serum ferritin level for diagnosing IDA.Results There were 100 children in our study, consisting of 51boys and 49 girls with a mean age of 9.1 (SD 2.02) years. From the receiver-operator curve (ROC) curve analysis, the area under the curve (AUC) was 91.5)010 for a Mentzer index cutoff point of 13.51. Diagnostic test analysis revealed a sensitivity of93%, specificity 84 %, and accuracy 90%.Conclusion Mentzer index has good validity as an inexpensive and simple screen for IDA in 6-12-year-old children with hypochromic-microcytic anemia.